Characteristics of low-profile cross-ventilated freestalls - Joseph P. Harner; John F. Smith; R. Millner (Kansas Agricultural Experiment Station Research Reports, 2006)
The first low-profile cross-ventilated (LPCV) freestall building was stocked in fall 2005 in North Dakota. There currently are 3 other LPVC freestalls operational and 6 others under construction. The LPCV building offers some of the advantages of natural ventilated and tunnel ventilated freestalls. Natural or conventional tunnel ventilation buildings normally have from 2 to 6 rows of freestalls. The first LPCV building was an 8-row con-figuration, but wider LPCV buildings with 10, 12, 16, or 24 rows of freestalls are being con-sidered. Low-profile cross-ventilated freestall buildings are another option for dairy cattle housing. These facilities allow producers to have more control over the cow's environment during all seasons of the year. They also al-low cows to be located closer to the milking parlor, reducing time away from feed and wa-ter.; Dairy Day, 2006, Kansas State University, Manhattan, KS, 2006;
Keywords: Dairy Day; 2006; Kansas Agricultural Experiment Station contribution; no. 07-118-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 965; Dairy; Cooling systems; Cross ventilation